Chicamocha canyon wind energy potential and VAWT airfoil selection through CFD modeling - Luis Fernando García-Rodríguez; Julian E. Jaramillo; Jorge Luis Chacón Velasco (Revista Facultad de Ingeniería Universidad de Antioquia)
The use of vertical axis wind turbines (VAWT) in Colombia could tackle the energy distribution difficulties as large parts of the territory are not connected to the electrical grid. The present research experimentally determines the wind resource available of a rural place known as Chicamocha’s canyon and selects the airfoil for a VAWT blade through CFD modeling. By using the mean wind speed of the location, the performance of the NACA0018 and DU06W200 airfoils is evaluated in terms of the lift and drag coefficients through a 2D CFD modeling using OpenFOAM and the “Spalart-Allmaras fv3” turbulence model. It is found feasible the use of wind energy at the location where the mean year density power is 485 [W/m2], and the DU06W200 airfoil is suggested for constructing the blades of a VAWT, as its aerodynamic efficiency (cl/cd) overcomes by 14% the commonly used NACA0018.